Inflammation‐induced hepatocellular carcinoma is dependent on CCR5 in mice. Issue 3 (12th July 2013) - Barashi, Neta; Weiss, Ido D.; Wald, Ori; Wald, Hanna; Beider, Katia; Abraham, Michal; Klein, Shiri; Goldenberg, Daniel; Axelrod, Jonathan; Pikarsky, Eli; Abramovitch, Rinat; Zeira, Evelyne; et al.
<x xml:space="preserve">Abstract</x> Human hepatocellular carcinoma (HCC) is an inflammation‐induced cancer, which is the third‐leading cause of cancer mortality worldwide. We investigated the role of the chemokine receptors, CCR5 and CCR1, in regulating inflammation and tumorigenesis in an inflammation‐induced HCC model in mice. Multidrug resistance 2 gene (Mdr2)‐knockout (Mdr2‐KO) mice spontaneously develop chronic cholestatic hepatitis and fibrosis that is eventually followed by HCC. We generated two new strains from the Mdr2‐KO mouse, the Mdr2:CCR5 and the Mdr2:CCR1 double knockouts (DKOs), and set out to compare inflammation and tumorigenesis among these strains. We found that in Mdr2‐KO mice lacking the chemokine receptor, CCR5 (Mdr2:CCR5 DKO mice), but not CCR1 (Mdr2:CCR1 DKO), macrophage recruitment and trafficking to the liver was significantly reduced. Furthermore, in the absence of CCR5, reduced inflammation was also associated with reduced periductal accumulation of CD24+ oval cells and abrogation of fibrosis. DKO mice for Mdr2 and CCR5 exhibited a significant decrease in tumor incidence and size. Conclusions: Our results indicate that CCR5 has a critical role in both the development and progression of liver cancer. Therefore, we propose that a CCR5 antagonist can serve for HCC cancer prevention and treatment. (Hepatology 2013;53:1021–1030)